O turismo e a paisagem natural e cultural do Parque Estadual da Serra do Mar - Núcleo Santa Virgínia - Lazarim, Pedro Vicente Moura [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Tourism represents a socio-economic activity to generate local and regional development and at the same time contribute to the valuation and conservation of natural and cultural landscape. From this premise, we believe that the study area - PESM – Núcleo Santa Virginia and surroundings - has a great tourism potential, which can be further explored through public policies that value and at the same time assist the conservation of the natural and cultural landscape of the region. Therefore, this project, which arises from a research project conducted by the National Council for Scientific and Technological Development (CNPq) in partnership with the Forestry Institute (IF), analyzes the possibilities and limitations of the attractions and tourist activities in areas of intensive, extensive use and around this area. Through literature research and application of semi-structured questionnaires to the main agents of local tourism important information for the characterization of tourism activities in the study area were obtained, as well as to identify gaps in planning instruments and management about PESM - Núcleo Santa Virginia. Through this diagnosis, we intend to provide support for the development of tourism in Núcleo Santa Virginia and its surrounding area, seeking to conserve natural and cultural heritage and improving the quality of life of local people

O turismo representa uma atividade socioeconômica capaz de gerar desenvolvimento local e regional e, ao mesmo tempo, contribuir para a valoração e conservação da paisagem natural e cultural. A partir desta premissa, acreditamos que a área de estudo – PESM – Núcleo Santa Virgínia e entorno- apresenta um grande potencial turístico, que pode ser ainda mais explorado através de políticas públicas que valorizem e ao mesmo tempo auxiliem a conservação da paisagem natural e da paisagem cultural da região. Sendo assim, o presente projeto, que surge a partir de um projeto de iniciação científica realizado através do Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq) em parceria com o Instituto Florestal (IF), analisa as potencialidades e as limitações dos atrativos e das atividades turísticas desenvolvidas nas áreas de uso intensivo, extensivo e no entorno desta área. Através do levantamento bibliográfico documental e da aplicação de questionários semiestruturados dirigidos aos principais agentes ligados ao turismo foram coletadas informações importantes para a caracterização das atividades turísticas na área de estudo, assim como, para identificar as lacunas dos instrumentos de planejamento e gestão acerca do PESM – Núcleo Santa Virgínia. Por meio deste diagnóstico pretendemos fornecer subsídios para o desenvolvimento do turismo nas áreas de entorno do Núcleo Santa Virgínia, objetivando a conservação do patrimônio natural e cultural e a melhoria da qualidade de vida da população local
Keywords: Ecologia; Ecoturismo; Patrimônio cultural; Política ambiental; Conservação da natureza; Proteção ambiental; Núcleo Santa Virgínia (Parque Estadual da Serra do Mar, SP); Parque Estadual da Serra do Mar (SP)